GENERAL SCIENTIFIC PRINCIPLES OF PEDAGOGICAL RESEARCH (Web of Teachers: Inderscience Research, 2025)
This article examines the principles of research activity in methodological knowledge, its objective patterns, factors influencing a researcher's expertise, the most important decisions previously analyzed in the study, forecasting the development of pedagogical phenomena and processes, and the difference between historical-pedagogical and theoretical-pedagogical research. The article also discusses various aspects of the functioning and development of the socio-pedagogical process, its elements, relationships, and the diversity of internal and external factors, while justifying the need for its systematic study.